GEOGRAPHICAL IDENTIFICATION OF DURIAN (CV. MONTHONG) FROM PRACHUAP KIRI KHAN AND CHANTHABURI PROVINCE BY USING NEAR INFRARED SPECTROSCOPY - Kingdow CHANACHOT; Wanphut SAECHUA; Panmanas SIRISOMBOON (My University, 2021)
Geographic origin of durian (Durio zibethinus Murray) can influence consumers purchasing decisions. A guaranteed geographical origin is extremely useful to maintain the credibility and popularity of this fruit. The objective of this work is to confirm geographical identification (GI) of durian Monthong from Prachuap Kiri Khan Province from south of Thailand which achieved the GI lable from the department of intellectual property by near infrared spectroscopy (NIRs). Total of 60 durian Monthong samples were acquired in the wavenumber range of 12,500-4,000 cm<sup<-1</sup< by FT-NIR spectrometer. The sample presentation for scanning were 3 forms including intact peel (with thorns), cut-thorns peel and stem of the fruit. Soft independent modeling of class analogy (SIMCA), partial least squares discriminant analysis (PLS-DA) and support vector machine classification (SVMC) were used to establish identification model using the full spectra. Overall classification accuracy of SVMC was the highest in training and validation set of stems which was 100% and 100%, respectively. This study indicated that NIRs might be a method to guaranteed geographic origin of durian Monthong from Prachuap Kiri Khan. However, more robust model should be developed by using more samples.
Keywords: Spectroscopy and Chemometric Analyses